Fostering self-regulated learning through ICT - Dettori, Giuliana, 1955-; Persico, Donatella, 1957- (Information Science Reference, 2011)
"This book presents the relationship between SRL and ICTs from several standpoints, addressing both theoretical and applicative issues, providing examples from a range of disciplinary fields and educational settings"--Resumé vydavatele
Keywords: technologie vzdělávání; informační a komunikační technologie ve vzdělávání; počítačem podporovaná výuka; autoregulace učení; educational technology; information and communication technologies in education; computer-aided learning; self-regulated learning; příručky; handbooks and manuals